GRAMMATICAL OVERGENERALIZATION MADE BY LEVEL 1 LEARNERS OF FIRDAUS ENGLISH COURSE (FEC) PATIANROWO, NGANJUK - Adi Yusuf (Universitas Pesantren Tinggi Darul Ulum Jombang, 2012)
Adi Yusuf University of Pesantren Tinggi Darul Ulum Jombang Adi_yoesop@yahoo.co.id Abstract Besides the influence of first language (L1), learnersâ€™ poor knowledge of second language (L2) often leads to mistakes (errors). The phenomenon of second language acquisition errors (L2) caused by the second language (L2) is called overgeneralization (negative intralingual transfer). This study describes grammatical overgeneralization often made by Level 1 students' of Paradise English Course (FEC) Patianrowo, Nganjuk and the factors causing them. The errors at least can be categorized into twelve kinds of errors: tense-related errors, modal-related errors, infinitive-related errors, gerund-related errors, present participle-related errors, noun clause-related errors, pronoun-related errors, article-related errors, preposition-related errors, singular and plural-related errors, and word order-related errors. Those errors are caused by two aspects, they are inductive and deductive reasoning. Keywords: transfer, intralingual transfer (overgeneralization), level 1 students Â Abstrak Selain bahasa pertama (L1), pengetahuan pembelajar yang buruk tentang bahasa kedua (L2) sering menyebabkan mistakes (errors). Fenomena kesalahan akuisisi bahasa kedua (L2) yang disebabkan oleh bahasa kedua (L2) disebut overgeneralization (transfer intralingual negatif). Studi ini menggambarkan tata bahasa overgeneralization yang sering dilakukan oleh para siswa tingkat 1 di Firdaus English Course (FEC) Patianrowo, Nganjuk dan faktor-faktor penyebabnya. Errors setidaknya dapat dikategorikan menjadi dua belas jenis: tense-related errors, modal-related errors, infinitive-related errors, gerund-related errors, present participle-related errors, noun clause-related errors, pronoun-related errors, article-related errors, preposition-related errors, singular and plural-related errors, and word order-related errors. Kesalahan-kesalahan disebabkan oleh dua aspek, yaitu penalaran induktif dan deduktif. Â Kata kunci: transfer, transfer intralingual (overgeneralisasi), siswa level 1